2020
DOI: 10.3390/su12010421
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Technology Transfer Preferences of Smallholder Farmers in Tunisia’s Arid Regions

Abstract: The objective of this research study was to assess the sources of information on two improved agricultural and livestock technologies (barley variety and feed blocks) as well as the efficacy of numerous agricultural technology diffusion means introduced in the livestock–barley system in semi-arid Tunisia. The research used primary data collected from 671 smallholder farmers. A descriptive statistical analysis was conducted, and Kendall’s W-test and the chi-squared distribution test were deployed to categorize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 18 publications
4
35
0
Order By: Relevance
“…Robust methodologies on how to standardize the PPB and PVS approaches for the myriad social and physical environments occupied by smallholder farmers are just emerging (e.g. Bentley, 1994 ; van de Fliert et al , 2002 ; Dhehibi et al , 2020 ). These methodologies are especially pertinent with respect to PPB, where the cost/benefit of breeding for the myriad distinct conditions of smallholder farmers has to be carefully weighted.…”
Section: Release and Adoption Of New Varietiesmentioning
confidence: 99%
“…Robust methodologies on how to standardize the PPB and PVS approaches for the myriad social and physical environments occupied by smallholder farmers are just emerging (e.g. Bentley, 1994 ; van de Fliert et al , 2002 ; Dhehibi et al , 2020 ). These methodologies are especially pertinent with respect to PPB, where the cost/benefit of breeding for the myriad distinct conditions of smallholder farmers has to be carefully weighted.…”
Section: Release and Adoption Of New Varietiesmentioning
confidence: 99%
“…In these demonstrations, the farmers can witness the outcome but cannot assess the gains. Assessing gain needs to set up a control plot planted with the next best option available with the same farmer-determined farming practices [5,150].…”
Section: Head-to-head Trials As Efficient and Innovate Means Of Demonmentioning
confidence: 99%
“…Head-to-head trials improve farmer's knowledge in the self-supervised plots. Large number of such trials for STRVs are being laid in farmers' fields that have revealed promising results against the counterfactuals in Eastern India [12,150]. These trials are being carried out through a network of KVKs apart from NGOs who have a strong presence in remote areas where extension services are not adequate.…”
Section: Head-to-head Trials As Efficient and Innovate Means Of Demonmentioning
confidence: 99%
“…The clientele's involvement in problem definition and solving could be addressed through improved market segmentation and the product development process of the chickpea improvement. There are several extension service approaches [71], but pluralistic and participatory approaches including farmer training, agricultural technology demonstrations, field days, and farmer-to-farmer interactions are generally considered effective agricultural extension methods [71,105,106]. In recent years, information and communication technologies (ICTs) have been promoted as a promising way for agricultural extension provision in smallholder production systems in developing countries [107].…”
Section: Taking Chickpea To the "Last Mile"mentioning
confidence: 99%